Additive Manufacturing Techniques for the Reconstruction of 3D Fetal Faces - Domenico Speranza; Daniela Citro; Francesco Padula; Barbara Motyl; Federica Marcolin; Michele Calì; Massimo Martorelli (Applied Bionics and Biomechanics)
This paper deals with additive manufacturing techniques for the creation of 3D fetal face models starting from routine 3D ultrasound data. In particular, two distinct themes are addressed. First, a method for processing and building 3D models based on the use of medical image processing techniques is proposed. Second, the preliminary results of a questionnaire distributed to future parents consider the use of these reconstructions both from an emotional and an affective point of view. In particular, the study focuses on the enhancement of the perception of maternity or paternity and the improvement in the relationship between parents and physicians in case of fetal malformations, in particular facial or cleft lip diseases.